Solar XXI: A Portuguese Office Building towards Net Zero-Energy Building - Goncalves, Helder (2012)
Solar Building XXI, built in 2006, at LNEG Campus in Lisbon, pretends to be an example of a low energy building using passive systems both for heating and cooling (ground cooling) towards a Net Zero-Energy Building (NZEB). The main façade has a PV system with heat recovery which assists the heating in winter time. In summer a ground cooling system (earth tubes)is used to cool the building, together with night cooling strategies. Net Zero-Energy Buildings Performance has gained more attention since the publication in 2010 of the EPBD recast. Successful implementation of such an ambitious target depends on a great variety of factors. For designers and code writers these include: balancing climate driven-demand for space cooling and heating with climate-driven supply for renewable energy resources. With a literature full of theoretical advice and a building industry rife with myths about the value of technologies,the present paper intends to unveil a sustainable framework for sharing insights into NZEB methodology applied to a Portuguese solar office building, SOLAR XXI, currently underway to reach the Net Zero-Energy Goal. Under the common work which is developed also in SHC Task 40-ECBCS Annex 52, “Towards Net Zero Solar Energy Buildings”, the authors of this paper are currently engaged in studying possible strategies for “upgrading” Solar XXI to NZEB status.